Assessment of Groundwater Quality and Hydrochemistry using Water Quality Index in District Mirpur Khas, Sindh, Pakistan - Arain, Ghulam Murtaza; Khatoon, Sumaira; Sattar, Nazia; Mustaquim, Javed (Asian Journal of Chemistry, 2024)
Groundwater is a major source of drinking water in the rural areas of Sindh province, including District Mirpur Khas of Pakistan. This study was undertaken to evaluate the suitability of groundwater in Mirpur Khas for drinking purposes. In October and November 2018, the groundwater samples were collected from 50 bore wells and analyzed 17 physico-chemical parameters. The pH ranged from 7.8 to 8.8, indicating the slightly alkaline nature of the water. The mean abundance of major cations is Na+ > Ca2+ > Mg2+ > K+ and for major anions, it is SO42– > Cl– > HCO3– > NO3– > F–. The hydrochemical facies of groundwater samples show that 29 have a mixed composition, Na+-K+-Cl– characterized by 17 and the remaining 4 fall into the Ca2+-Mg2+-HCO3– category. The water quality index (WQI) was calculated based on WHO standards for drinking water using 16 physico-chemical parameters. The computed WQI values range from 20.4 to 503.1. Out of the 50 samples, 9 are classified as ‘excellent,’ 21 as ‘good,’ 13 as ‘poor,’ 4 as ‘very poor,’ and 3 as ‘unsuitable for drinking.’ The average WQI value is 118.7 for 50 samples, which falls under the ‘good’ category. Turbidity and EC exhibited the highest mean effective weight values, indicating their significant influence on the WQI values.